Perception of Urban Population on Herbal Plants Information Presentation in Televisionâ€™s Talk show Program - Dida, Susanne; Setianti, Yanti; C. Priyatna, Centurion; Ari Agung Prastowo, FX. (International Journal of Engineering and Technology, 2018)
The purpose of this research is to explore the needs of urban population on herbal plant television program and producing an ideal outline of herbal plant television program. Based on the previous research as a starting point, it is revealed that level of trust from people towards herbal plants, as one of the heritage from past, are still high. This occurs as people believe that herbal plants have been identified as a cure for some diseases in a very long period of time. This research uses a descriptive method, which applied to explain a particular event. Preliminary data shows that the trust level on herbal plants is higher, owing to the fact that herbal plants is considered to be cheaper and purely without additional chemical ingredients. Other than that, herbal plants are also believed to be able to compete, in term of quality and the health effect, with pharmaceutical-grade medicine prescribed by doctors. The result shows that the perception towards talk-show program is positive, caused by, basically, the need of information on herbal plants. It is established that the benefit of talk-show program is valued highly, which must be maintained by the use of credible experts on herbal plants in the talk-show.Â Â